독립적인 이중 출력을 갖는 DC-DC 컨버터의 해석 및 설계 - 許泰遠(Tae-Won Heo); 朴志浩(Ji-Ho Park); 金?完(Dong-Wan Kim); 禹靖仁(Jung-In Woo) (전기학회 논문지 P권, 54(4), 2005)
The proposed dual-output DC-DC converter that bases on flyback converter can obtain two output voltage with non-isolated main-output and isolated sub-output at the same time using single-winding high frequency transformer. It can solve problems in multi-winding converter that use one main-switch, and also control quality of isolated sub-output voltage can be improved by additional sub-switch to the second. For analysis and design of the proposed converter system, converters are classified as operation mode from switching state and are become modeling by applying state space averaging method. Steady-state characteristics and dynamic characteristics are analyzed by DC component and perturbation component from state space averaging model. From experiment converter, validity of analysis and design for the propose converter system is confirm.